Estimating the Determinants of Demand for Cosmetic Face Care Products - Fran Galetić; Nika Požega (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Cosmetic industry plays an important role in every developed economy. The market for cosmetic products is growing at an average annual rate between 4% and 5%. The total revenue in cosmetic industry in 2018 was over 260 billion euro. Cosmetic market is composed of several categories: skincare, hair care, make-up, perfumes, toiletries and deodorants, and oral cosmetics. Skincare is the leading category, accounting for about 36 percent of the global cosmetic market. In this paper we analyze the most important segment of skincare – face care. The idea of this paper is to estimate the determinants of demand for cosmetic face care products. To find this out, we have conducted a survey in which the respondents gave their answers about their habits and desires in the process of buying and using face care cosmetic products.
Keywords: 650; cosmetic industry; demand; face care; survey